(untitled) (GAIMS Journal of Medical Sciences, 2026)
Background: ADHD causes high rates of co morbidities such as mood and anxiety disorders, substance use disorders etc. This study aims to assess the prevalence of knowledge and misconceptions in people who are in close contact with young children and to understand the impact of ADHD on quality of life among late diagnosed ADHD individuals. Material and Methods: This is a community based cross sectional study done on 419 study subjects (parents -197, teachers -175, Anganwadi workers–47) in the urban field practice area of a tertiary care medical college during November and December 2023. For assessing the quality of life of the 30 late diagnosed ADHD individuals, were identified and in-depth interviews were conducted. Results: None of the Anganwadi workers had adequate knowledge about ADHD. Majority of the parents (58.8%) and teachers (52%) had no knowledge about ADHD. Majority of the study subjects felt that symptoms of ADHD could be overcome by “willpower”. Most common attitudinal problem among anganwadi workers was that it’s not a real medical problem. Most common themes to emerge in the in-depth interviews was the problem in maintaining a career and lack of societal understanding. Conclusion: Training of care givers in early identification of ADHD symptoms is essential.